The Effect Of The Implementation Of History Video Media On Students' Learning Outcomes In The Subject Of History At State Senior High School 1 Banyuasin 1 - Desky Suhendra; Supriyanto Supriyanto; SaniSafitri Safitri (Sriwijaya University in collaboration with Perkumpulan Program Studi Pendidikan Sejarah Se-Indonesia (P3SI) dan Masyarakat Sejarawan Indonesia (MSI)., 2019)
This study is entitled